Precision oncology revolution: CRISPR-Cas9 and PROTAC technologies unleashed - Kanbar, Karim; El Darzi, Roy; Jaalouk, Diana E. (Frontiers in Genetics, 2024)
Cancer continues to present a substantial global health challenge, with its incidence and mortality rates persistently reflecting its significant impact. The emergence of precision oncology has provided a breakthrough in targeting oncogenic drivers previously deemed "undruggable" by conventional therapeutics and by limiting off-target cytotoxicity. Two groundbreaking technologies that have revolutionized the field of precision oncology are primarily CRISPR-Cas9 gene editing and more recently PROTAC (PROteolysis TArgeting Chimeras) targeted protein degradation technology. CRISPR-Cas9, in particular, has gained widespread recognition and acclaim due to its remarkable ability to precisely modify DNA sequencesto modify DNA sequences precisely. Rather than editing the genetic code, PROTACs harness the ubiquitin proteosome proteasome degradation machinery to selectively degrade proteins of interestto degrade proteins of interest selectively. Even though CRISPR-Cas9 and PROTAC technologies operate on different principles, they share a common goal of advancing precision oncology whereby both approaches have demonstrated remarkable potential in preclinical and promising data in clinical trials. CRISPR-Cas9 has demonstrated its clinical potential in this field due to its ability to modify genes directly and indirectly in a precise, efficient, reversible, adaptable, and tissue-specific manner, and its potential as a diagnostic tool. On the other hand, the ability to administer in low doses orally, broad targeting, tissue specificity, and controllability have reinforced the clinical potential of PROTAC. Thus, in the field of precision oncology, gene editing using CRISPR technology has revolutionized targeted interventions, while the emergence of PROTACs has further expanded the therapeutic landscape by enabling selective protein degradation. Rather than viewing them as mutually exclusive or competing methods in the field of precision oncology, their use is context-dependent (i.e., based on the molecular mechanisms of the disease) and they potentially could be used synergistically complementing the strengths of CRISPR and vice versa. Herein, we review the current status of CRISPR and PROTAC designs and their implications in the field of precision oncology in terms of clinical potential, clinical trial data, limitations, and compare their implications in precision clinical oncology.